EXPERIMENTAL AND THEORETICAL INVESTIGATIONS FOR BEHAVIOR OF PRECAST CONCRETE GIRDERS WITH CONNECTIONS (Journal of Engineering, 2012)
This research presents experimental and theoretical investigation of 15 reinforced concrete spliced and nonspliced girder models. Splices of hooked dowels and cast in place joints, with or without strengthening steel plates were used. Post-tensioning had been used to enhance the splice strength for some spliced girders. The ANSYS computer program was used for analyzing the spliced and non-spliced girders. A nonlinear three dimensional element was used to represent all test girders. The experimental results have shown that for a single span girder using steel plate connectors in the splice zone has given a sufficient continuity to resist flexural stresses in this region. The experimental results have shown that the deflection of hooked dowels spliced girders is greater than that of non-spliced girder in the range of (17%-50%) at about 50% of the ultimate load which approximately corresponds to the serviceability limit state and the ultimate loads is less than that of non-spliced girder in the range of (12%-52%). For other spliced girders having strengthening steel plates at splices, the results have shown that the deflection of the spliced girder is less than that of non-spliced girder in the range of (2%-20%) at about 50% of the ultimate load and the ultimate loads for spliced girder is greater than that of nonspliced girder in the range of (1%-7%). The post-tensioned concrete girders have shown a reduction in deflection in the range of (26% - 43%) at a load of 50% of the ultimate load as compared with that of ordinary girders. Moreover, post-tensioning increases the ultimate loads in the range of (70% - 132%). The results obtained by using the finite element solution showed a good agreement with experimental results. The maximum difference between the experimental and theoretical ultimate loads for girders was in the range of (3-11%).